Atrial Fibrillation in Autoimmune Rheumatic Diseases: from Pathogenesis to Treatment - Ciconte, Giuseppe; Conti, Manuel; Evangelista, Martina; Pappone, Carlo (Reviews on Recent Clinical Trials, 2018)
Atrial Fibrillation (AF) is the most commonly described cardiac arrhythmia found in the general population and can lead to adverse outcomes. Its onset and maintenance requires the presence of an arrhythmogenic substrate that predisposes the patient for risk of these types of arrhythmias and the occurrence of a trigger event. A major characteristic of AF-related structural remodelling is atrial fibrosis, a process closely related to inflammation. Autoimmune rheumatic diseases constitute systemic inflammatory disorders that can also present with cardiovascular manifestations, including a high incidence of AF, thus supporting the idea of a link between AF and inflammation. A vicious cycle exists in which inflammation leads to a higher prevalence of structural cardiovascular disease, which in turn leads to more inflammation and AF; in fact, inflammation is known to affect signalling pathways that lead to the development of AF. Therapy must first target systemic inflammation, since decreasing the inflammatory burden has consistently shown to positively ameliorate the prognosis. When this approach is not sufficient, rhythm or, when not feasible, rate control is indicated in addition to anticoagulant therapy. As far as the rhythm control strategy is concerned, antiarrhythmic drugs and/or catheter ablation should be considered. New mapping techniques allowing the characterization of the arrhythmic substrate have opened new perspectives and may help in the treatment of AF in these patients, since atrial tissue is the target of inflammation-induced arrhythmic alterations. In cases where the natural history of the arrhythmia itself is more advanced, in order to minimize the impact of AF on cardiac function as well as quality of life, a device-based therapy, including an “ablate and pace” approach could be adopted.
Keywords: mapping techniques